On the measurement of dislocations and dislocation substructures using EBSD and HRSD techniques. (15th August 2019) - Muránsky, O.; Balogh, L.; Tran, M.; Hamelin, C.J.; Park, J.-S.; Daymond, M.R.
Abstract: The accumulation of the dislocations and development of dislocation structures in plastically deformed Ni201 is examined using dedicated analyses of Electron Back-Scatter Diffraction (EBSD) acquired orientation maps, and High-Resolution Synchrotron Diffraction (HRSD) acquired patterns. The results show that the minimum detectable microstructure-averaged (bulk) total dislocation density ( ρ T ) measured via HRSD is approximately 1E13 m −2, while the minimum GND density ( ρ G ) measured via EBSD is approximately 2E12 m −2 – the EBSD technique being more sensitive at low plastic strain. This highlights complementarity of the two techniques when attempting to quantify amount of plastic deformation (damage) in a material via a measurement of present dislocations and their structures. Furthermore, a relationship between EBSD-measured ρ G and the size of HRSD-measured Coherently Scattering Domains (CSDs) has been mathematically derived – this allows for an estimation of the size of CSDs from EBSD-acquired orientation maps, and conversely an estimation of ρ G from HRSD-measured size of CSDs. The measured evolution of ρ T, and ρ G is compared with plasticity theory models – the current results suggest that Ashby's single-slip model underestimates the amount of GNDs ( ρ G ), while Taylor's model is correctly predicting the total amount of dislocation ( ρ T ) present in the material as a function of imparted plastic strain. Graphical abstract: Image 1